RANCANG BANGUN APLIKASI PENENTUAN TINGKAT RISIKO PENYAKIT GASTROESOFAGEAL REFLUX DISEASE (GERD) BERDASARKAN POLA MAKAN, GAYA HIDUP, DAN STATUS GIZI DENGAN POHON KEPUTUSAN KONSEP ENTROPY - Hambali Furnawan; Sukma Puspitorini (JURNAL AKADEMIKA)
Gastroesophageal Reflux Disease (GERD) is a gastrointestinal disease in which oesophageal abnormalities that cause gastric fluid to flow back (reflux) into the esophagus and cause heartburn symptoms typical of burning in the chest, sometimes accompanied by pain. GERD can be experienced by any person at any time and in intensity which often can cause the inflammation of the esophagus esofagistis (esophagus) which can lead to complications such as esophageal stricture, Barrett's esophagus, and esophageal cancer. Lifestyle factors and good eating habits can be the cause of GERD. This GERD disease risk level determination aplication programme design is made to determine the extent of a person's risk of experiencing GERD seen lifestyle factors, diet, and nutritional status as well. Data obtained from questionnaires given to patient. The average point on each variable for lifestyle factors and diet then categorized. While the nutritional status is obtained by finding a body mass index (BMI) of the patient. Of the categories obtained on each factor, the classification rule set (classification rule) which will then be represented in the form of a decision tree (decision tree). The results obtained from a search result is a tree-level person's risk of disease GERD.